2017
DOI: 10.1007/s11240-017-1240-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of inside and outside factors to improve recombinant protein yield in plant

Abstract: an improvement of critical features, including transcription, translation and post-translational modifications, in plant cells could make plant systems a safe and economical alternative for biopharmaceutical production. Hence, in this review, the most recent advances influencing the upstream and downstream processes involved in recombinant protein accumulation in plant cells are described. We also discuss how plant systems are becoming the benchmark for the production of several biopharmaceuticals.Keywords Het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 191 publications
(180 reference statements)
2
15
0
Order By: Relevance
“…Transient gene expression based on agroinfiltration is an efficient, cost-effective and time-saving strategy for obtaining high amounts of recombinant proteins, as stable genetic transformation is a slow process and requires months or years to generate transgenic plants due to regeneration protocols. In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Transient gene expression based on agroinfiltration is an efficient, cost-effective and time-saving strategy for obtaining high amounts of recombinant proteins, as stable genetic transformation is a slow process and requires months or years to generate transgenic plants due to regeneration protocols. In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54].…”
Section: Discussionsupporting
confidence: 89%
“…Using this system, the need for plasmid delivery based on complicated methods of generating RNA is eliminated. The MagnICON system provides an efficient system without functional infectious proteins because of the deletion of the CP gene, whereas the yield and speed of viral system are maintained [22].…”
Section: Introductionmentioning
confidence: 99%
“…The yield obtained in this work, 203 mg of NS1DENV2 per kilogram of fresh leaf, showed that the plant expression system used was efficient and consistent with other systems aimed at optimizing the production of recombinant protein, which obtained, respectively, 70 mg/kg and 24.5 mg/kg (Fedosov et al, 2003;Rigano et al, 2004;Yang et al, 2015;Habibi et al, 2017;Okay and Sezgin, 2018). In their work, Jeong et al (2018) demonstrated that it is possible to achieve overexpression of the mCherry protein (0.4 mg) per g of Arabidopsis callus.…”
Section: Discussionsupporting
confidence: 80%
“…Plant secondary metabolites are involved in the adaptation of plants to their environment, and most of these metabolites are involved in plant defence mechanisms against pathogen invasion and abiotic stress (Habibi et al ., 2017b). These valuable compounds could be extracted from different parts of plants, such as leaves, shoots, roots and flowers, and investigated for their potential as anti‐HIV and anti‐TB drugs.…”
Section: Natural Sources Of Plant Metabolites With Anti‐hiv and Tb Acmentioning
confidence: 99%
“…Expression systems also have been developed based on other plants such as rice, carrot, maize, Spinach, lettuce (Chan and Daniell, 2015;Lakshmi et al,2013), cowpea, potato, Arabidopsis (Scotti et al, 2010) and moss (Orellana-Escobedo et al, 2015) for the production of recombinant HIV and TB antigens. Advantages and disadvantages of these systems are reviewed elsewhere by Habibi et al (2017b).…”
Section: Advantages and Obstaclesmentioning
confidence: 99%